Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Killing the Black Body: race, reproduction, and the meaning of liberty - Roberts, D. (Pantheon, 1997)
Keywords: 1900-1999; 1980-1989; 1990-1999; afro-féminisme; amérique du nord; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; histoire et politique; inégalités; justice reproductive; périodes historiques; racisme; régions géographiques; sciences humaines; sexisme; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Méthodologie féministe pour les femmes et le développement : concepts, contextes et pratiques dans L'égalité devant soi: sexes, rapports sociaux et développement international - Dagenais, Huguette (L'égalité devant soi: sexes, rapports sociaux et développement international, 1994)
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; cours; discipline; féminisme décolonial; histoire et politique; pol4022; premier cycle; périodes historiques; racisme; régions géographiques; science politique; sexisme; système colonial; systèmes d'oppressions; thématiques

Outlaw culture: Resisting representations - hooks, bell (Routledge, 1994)
Keywords: 1900-1999; 1980-1989; 1990-1999; afro-féminisme; amériques; approches et analyses; féminismes noirs; périodes historiques; racisme; représentations; représentations médiatiques; régions géographiques; sexisme; systèmes d'oppressions; états-unis

Frontiers: Selected essays and writings on racism and culture, 1984-1992 - Philip, Marlene Nourbese (Mercury Press, 1992)
Cette collection d'essais tant attendue se compose d'écrits sélectionnés parmi les nombreuses apparitions de la boursière Guggenheim Marlene Nourbese Philip dans des magazines, des journaux et des revues, y compris FUSE . Mordant, élégant, tour à tour farouchement interrogateur, magiquement lyrique et doucement explorateur, l'examen par Philip des questions contemporaines de race et de culture est toujours éloquent et impérieux.
Keywords: 1900-1999; 1980-1989; 1990-1999; amériques; approches et analyses; arts; cours; discipline; fem1000; inégalités; littérature; premier cycle; périodes historiques; racisme; régions géographiques; systèmes d'oppressions; états-unis; études littéraires

Homeplace : a site of resistance dans Yearning: race, gender, and cultural politics - Hooks, Bell (Yearning: race, gender, and cultural politics, 1990)
bell hooks crosses boundaries in major debates on postmodern theory, cultural criticism, and the politics of race and gender. She warns that “discourse” about “difference” is dangerously detachable from more essential struggles.
Keywords: 1900-1999; 1980-1989; afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; cours; discipline; féminisme afroaméricain; histoire et politique; patriarcat; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; violences; états-unis